(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This scientific article discusses the problems associated with the ecological infrastructure of modern cities and, based on the analysis, draws conclusions and recommendations for the organization, improvement and development of the ecological infrastructure of modern cities.